Investigating nanomotion-based technology (Resistell AST) for rapid antibiotic susceptibility testing among adult patients admitted to a tertiary-care hospital with Gram-negative bacteraemia: protocol for a prospective, observational, cross-sectional, single-arm study. Issue 11 (21st November 2022) - Caruana, Giorgia; Kritikos, Antonios; Vocat, Anthony; Luraschi, Amanda; Delarze, Eric; Sturm, Alexander; Pla Verge, Marta; Jozwiak, Grzegorz; Kushwaha, Samidha; Delaloye, Julie; Cichocka, Danuta; Greub, Gilbert
Abstract : Introduction: Effective treatment of bloodstream infections (BSIs) is relying on rapid identification of the causing pathogen and its antibiotic susceptibility. Still, most commercially available antibiotic susceptibility testing (AST) methods are based on monitoring bacterial growth, thus impacting the time to results. The Resistell AST is based on a new technology measuring the nanomotion caused by physiologically active bacterial cells and detecting the changes in nanomotion caused by the exposure to a drug. Methods and analysis: This is a single-centre, prospective, cross-sectional, single-arm diagnostic accuracy study to determine the agreement of the Resistell AST on Gram-negative bacteria isolated from blood cultures among patients admitted to a tertiary-care hospital with the reference method. Up to 300 patients will be recruited. Starting with a pilot phase, enrolling 10%–20% of the subjects and limited to Escherichia coli BSI tested for ceftriaxone susceptibility, the main phase will follow, extending the study to Klebsiella pneumoniae and ciprofloxacin. Ethics and dissemination: This study has received ethical approval from the Swiss Ethics Committees (swissethics, project 2020-01622). All the case report forms and clinical samples will be assigned a study code by the local investigators and stored anonymously at the reference centre (Lausanne University Hospital). The results will be broadly distributed through conference presentations and peer-reviewed publications. Trial registration number: ClinicalTrials.gov Registry (NCT05002413 ).